Studies on traumatic proptosis in 22 dogs - Nema, A.; Purohit, S.; Kamal, T.; Shivani; Saran, A.; Sahu, S.K.; Yadav, J.S. (Indian Journal of Veterinary Surgery, 2025)
The present study included 22 dogs suffering from unilateral traumatic proptosis presented during the period from January 2023 to December 2024. Among different breeds, non-descript (72.73%, n=16) breed was the most affected. More number of cases (77.27%, n=17) were chronic, with fighting (68.18% n=15) as the major cause of proptosis. Male dogs (68.18%, n=15) were more commonly affected with proptosis than females. Animals of age group 0-2 yr were the most affected (72.73%, n=16), followed by 2-5 yr (18.18%, n=4) and >10 yr age groups. All cases of traumatic proptosis divided in two groups (groups I and II) underwent surgical management. In group I (n=6), globe replacement surgery (GRS) along with tarsorrhaphy was performed in five acute and one chronic case. In group II (n=16), trans-palpebral enucleation was done in all chronic cases. Complications following GRS included dorso-lateral strabismus, corneal ulceration and phthisis bulbi. The prognosis after globe replacement surgery was favourable in three dogs, fair in two dogs and unfavourable in one dog with phthisis bulbus condition. In trans-palpebral enucleation, no complications were noticed. To conclude, globe replacement surgery along with tarsorrhaphy was found appropriate in managing acute proptosis cases with favourable to fair prognosis; whereas trans-palpebral enucleation proved suitable for managing chronic proptosis cases without any complications.